Half-Sandwich Arene Ruthenium(II) Thiosemicarbazone Complexes: Evaluation of Anticancer Effect on Primary and Metastatic Ovarian Cancer Cell Lines - Seminay Guler; Seminay Guler; Hulya Ayar Kayali; Hulya Ayar Kayali; Hulya Ayar Kayali; Egemen Orkun Sadan; Betul Sen; Elif Subasi (Frontiers Media S.A., 2022)
In this study, we describe the synthesis, characterization and antiproliferative activity of three organo-ruthenium(II) half-sandwich complexes [RuCl(η6-p-cym)(N,S-L)]Cl (I, II, and III). To form these complexes, three thiosemicarbazone ligands (TSCs) were synthesized; L = 5-nitro-2-carboxyaldehyde-thiophen-N-methyl-thiosemicarbazone, (L1); 2-acetyl-5-bromo-thiophen-N-methyl-thiosemicarbazone, (L2) and 2-acetyl-5-bromo-thiophen-N,N-dimethyl-thiosemicarbazone, (L3). The isolated compounds were analyzed using spectroscopic techniques such as elemental analysis, conductance measurements, FT-IR, 1H NMR spectroscopy, MALDI-TOF mass spectrometry, and single-crystal XRD. Our results demonstrated that the synthesized thiosemicarbazone ligands (TSCs) are bound to the metal ion as a bidentate ligand that coordinates through the thiocarbonyl sulfur and azomethine nitrogen atoms in all complexes (I, II, and III). The X-ray crystal structures of L1 and L2 revealed that both compounds are crystallized in the triclinic crystal system with space group P-1. The biological potency of newly synthesized TSC ligands (L1, L2, and L3) and their corresponding ruthenium complexes (I, II, and III) were investigated on human primary ovarian (A2780) and human metastatic ovarian (OVCAR-3) cell lines. To get detailed information respecting antitumor properties, cytotoxicity, DNA/BSA binding affinity, cellular uptake, DNA binding competition, and trans-epithelial resistance measurement assays were performed. Our results demonstrate that newly synthesized ruthenium(II) complexes possess potential biological activity. Moreover, we observe that the ruthenium complexes reported here show anticancer activity on primary (A2780) and metastatic (OVCAR-3) ovarian cancer cells.